Kantian Transcendental Pessimism and Jamesian Empirical Meliorism - Pihlström, Sami (Con-Textos Kantianos. International Journal of Philosophy, 2020)
Kant’s philosophy was an important background for the pragmatist tradition, even though some of the major classical pragmatists, especially William James, were unwilling to acknowledge their debt to Kant. This essay considers the relation between Kant and James from the perspective of their conceptions of the human condition. In particular, I examine their shared pessimism, employing Vanden Auweele’s (2019) recent analysis of Kant’s pessimism and arguing that this is required by James’s meliorism (which is put forward as a middle-ground option between optimism and pessimism). A comparative inquiry into Kant’s and James’s views on the relation between ethics and religion is provided against this background of their shared philosophical anthropology.